2023
DOI: 10.3390/electronics12071730
|View full text |Cite
|
Sign up to set email alerts
|

A New Three-Way Incremental Naive Bayes Classifier

Abstract: Aiming at the problems of the dynamic increase in data in real life and that the naive Bayes (NB) classifier only accepts or rejects the sample processing results, resulting in a high error rate when dealing with uncertain data, this paper combines three-way decision and incremental learning, and a new three-way incremental naive Bayes classifier (3WD-INB) is proposed. First, the NB classifier is established, and the distribution fitting is carried out according to the minimum residual sum of squares (RSS) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The local model under the framework of the FTwNB algorithm is the 3WD-INB. The 3WD-INB was proposed by Yang et al [29]. The algorithm uses the idea of the three-way decision to realize the three-way classification of samples, making the classification process more in line with people's thought process.…”
Section: Ftwnb Local Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The local model under the framework of the FTwNB algorithm is the 3WD-INB. The 3WD-INB was proposed by Yang et al [29]. The algorithm uses the idea of the three-way decision to realize the three-way classification of samples, making the classification process more in line with people's thought process.…”
Section: Ftwnb Local Modelmentioning
confidence: 99%
“…The process for the three-way classification is completed through the parameters α and β (generally: 0 ≤ β ≤ α ≤ 1)), and the P(C c ), P C c , P v According to the derivation by Yang et al [29], the expressions of the POS domain, NEG domain and BND domain of the 3WD-INB are shown in (8). According to this classification rule, the three-way classification of sample x h can be realized.…”
Section: Three-way Classification Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The "Naïve Bayes Classifier" refers to straightforward probability-based classifier which utilizes Bayes' theorem with dependable assumptions of independence. It anticipates that the proximity or lack of a particular class component will depend on the proximity or lack of any other element [19]. Conditional probabilities are necessary for the Naive Bayes calculation.…”
Section: E Classifiers 1) Naïve Bayes (Nb)mentioning
confidence: 99%
“…Zhi et al [14] introduced a three-way concept for conflict analysis [15]. Three-way concept analysis was proposed in [15] by combining three-way decision theory [16][17][18][19][20] and formal concept analysis [21,22], with the ability of describing the properties that objects possess in common and those that they do not possess in common [23,24]. Zhi et al [14] analyzed the conflict relationships between agents and identified the binary relationships between sets of agents and sets of issues by using three-way concepts, and then analyzed the causes of conflict.…”
Section: Introductionmentioning
confidence: 99%